O processo de rualização e o sistema único de assistência social/Suas : uma interlocução necessária entre proteção social básica e proteção social especial - Machado, Simone Araújo (2012)
The process of subjects homelessness adults and families living on the streets, the deployment of SUAS in the city of Porto Alegre and its inserting these from the interface of Basic Social Protection and Special Social Protection is the central question of this dissertation, which has reflects on how the legal documents, that are directed to the Homeless Population, and they approach the subject of Process of Homelessness adults and families who are in this condition, considering processes of prevention, protection and social inclusion of this population segment. Therefore, there was documentary analysis in the documents establishing the National Social Assistance/PNAS and Unified Social Assistance System/SUAS, the National Policy on Population Inclusion of Homeless/PNIPSR, and the Municipal Plan to Combat Homeless/PMESR, which was supplemented by records of supervising and monitoring conducted in FASC, along with services that cater to this population. In the present study we used the dialectical-critical method, and the results show that it is necessary to mediate the dialectic view regarding social phenomenon, that takes shape in the homelessness process, overcoming a static reading of this process. It is necessary to recognize it as the product of multiple constraints, expressions of social issues. It is configured in matters multifactorial, with the time in which this condition is important category for analysis. The attempt to contribute to this discussion by suggesting concrete alternatives in the deployment of SUAS, to change the relationship between the interfaces shields was also highlighted in this study. It points up a significant difficulty in this dialogue, with a clear need to extend this debate shows that still fragmented and fragile little daring, especially with regard to the provision of services in both protections, to increase the effectiveness of care directed at these subjects